2021
DOI: 10.1177/1532673x211013479
|View full text |Cite
|
Sign up to set email alerts
|

Political Ambition and Constituent Service: Does Ambition Influence How Local Officials Respond to Electoral and Non-Electoral Service Requests?

Abstract: Theoretically, political ambitions paired with elections generate more responsive elected officials. In this paper, we test whether the progressive political ambitions of public officials affect whether and how they respond to their constituents by conducting a experimental audit study where local public officials receive both an electorally related service request and a generic service request. We combine their responses (or non-responses) with data from a survey of these public officials conducted months pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Although 90% of our respondents expressed openness to holding higher office, their likelihood of eventually running is much lower (Einstein et al 2018). Recent work finds limited effects of ambition on local politicians’ actions related to service provision (Dynes, Hassell, and Miles 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although 90% of our respondents expressed openness to holding higher office, their likelihood of eventually running is much lower (Einstein et al 2018). Recent work finds limited effects of ambition on local politicians’ actions related to service provision (Dynes, Hassell, and Miles 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Competition for local elected office is often absent; a study of nearly 8,000 mayoral elections held between 2000 and 2016 showed that over half were uncontested (Marschall, Lappie, and Williams 2017). Even without competition, incumbents who have ambition to hold higher office still might be motivated by voter preferences (Dynes, Hassell, and Miles 2021). Therefore, we hypothesized that a politician’s competitive context and political ambition would moderate their response to news coverage.…”
Section: Local News and The Incentive To Pandermentioning
confidence: 99%
“…2023). Personality and political ambition play a role (Dynes et al, 2021(Dynes et al, , 2023, conscientious individuals tend to favor burdens while those who are more open to experience are less so (Aarøe et al, 2021). Discrimination may also be an additional factor in whether increased burdens are imposed.…”
Section: Burdening Citizens and Damaging Administrative Credibility?mentioning
confidence: 99%
“…Variations in responsiveness may partially result from different institutional incentives (Hobolt and Klemmensen 2008;Soroka and Wlezien 2010), contextual dynamics (Ezrow and Hellwig 2014;Ezrow, Hellwig, and Fenzl 2020;Giger and Klüver 2016), or representational roles (Dynes, Hassell, and Miles 2018;Harden 2013). But responsiveness also varies according to the policy issue.…”
mentioning
confidence: 99%
“…Individuals with more expertise in a given area tend to have more confidence in their own beliefs in that domain (Dunning 2005;Fisher and Keil 2016;Tetlock 2005) and to be less open to different views (Ottati et al 2015). Self-confidence and dogmatism may lead politicians with expertise in a specific domain to disregard opposing views on that issue.…”
mentioning
confidence: 99%